2022
DOI: 10.1126/sciadv.abl8214
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity reduces satellite-observed phenological variability in wetlands at a national scale

Abstract: Plant diversity may enhance stability of ecosystem function and its satellite-derived indicators. However, its potential to stabilize phenology, or seasonal changes in plant function, is little understood, especially in understudied systems with high biodiversity potential such as wetlands. Using a large sample of U.S. wetlands and a new satellite-based indicator of phenological stability, we found that plant diversity was negatively associated with interannual phenological variability after controlling for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…This can even be strong enough, at least for the completion of leaf development (LUen) and the overall duration (LUdur), to be valid across species (Figure 3). An indication of the generality of this response can be found in a remote sensing based study of US wetlands that showed phenological variability to be lower in warmer and wetter climates (Dronova et al., 2022). It has also earlier been demonstrated that in rapidly warming springs, the variability of budburst timings is lower than in colder springs (Denéchère et al., 2019).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This can even be strong enough, at least for the completion of leaf development (LUen) and the overall duration (LUdur), to be valid across species (Figure 3). An indication of the generality of this response can be found in a remote sensing based study of US wetlands that showed phenological variability to be lower in warmer and wetter climates (Dronova et al., 2022). It has also earlier been demonstrated that in rapidly warming springs, the variability of budburst timings is lower than in colder springs (Denéchère et al., 2019).…”
Section: Discussionmentioning
confidence: 93%
“…This would lead to differences in budburst timing for the same species (and provenance) in monospecific and multi‐species stands, despite the same macroclimatic spring weather conditions. A study in US wetlands linked plant species richness to a reduction in (satellite derived) phenological variability which indicated a complex relationship between phenology, climatic conditions and edaphic factors (Dronova et al., 2022). Also in grasslands, an experimental reduction in grass species diversity led to an earlier flowering phenology in most grass species (Wolf et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, below-ground biodiversity (soil biodiversity) altered grassland-ecosystem resistance and resilience through direct and indirect effects on plant diversity, net ecosystem productivity and plant species interactions, and, thus, changed grassland ecosystem stability [ 180 ]. In addition, recent studies have shown that phenological variation can also reconcile plant diversity with the seasonal stability of ecosystems, and, thus, affect the stability of the whole ecosystem [ 181 ].…”
Section: Resultsmentioning
confidence: 99%
“…The red‐edge and near‐infrared (700–1000 nm) regions offer better predictions of chlorophyll content and canopy biomass, while the short‐wave infrared (SWIR; >1500 nm) reveals cell water content and structural traits like cellulose content (Serbin & Townsend, 2020). Multispectral reflectance measures capture phenotypic differences amongst individuals, accounting for functional composition within an area and enabling accurate tracking of functional responses over time (Dronova et al., 2022; Dronova & Taddeo, 2022; Williams et al., 2021). Spectral metrics have been used to predict ecosystem functioning, similar to other measures, such as phylogenetic or functional diversity (Schweiger et al., 2018).…”
Section: Introductionmentioning
confidence: 99%